Literature Review : Faktor-Faktor Yang Mempengaruhi Anemia Pada Ibu Hamil - Wahyu Ernawati; Dwi Andarwati; Allania Hanung; Reffy Dhamayanti (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Globally the prevalence of anemia in pregnant women worldwide is 40%. The prevalence of anemia in pregnant women in Indonesia in 2018 increased by 48.9% compared to 2013 of 37.1% of pregnant women with anemia. Anemia is a major health problem. pregnant women who experience anemia can experience complications during childbirth, LBW and morbidity in mother and baby. The purpose of the literature review is to review the factors that influence anemia in pregnant women from various research results. The research used the literature review method. The database used for this research journal is from the Pubmed Central (PMC)/Pubmed, Science Direct, and Google Scholar databases. using the keywords "Factors" OR "affecting" OR "anemia" OR "in pregnancy". After the screening process, 5 journals relevant to the research topic were obtained. The results of the review on research on the factors that influence anemia in pregnant women are arranged based on grouping themes, namely internal factors, external factors, sociodemographic factors. The conclusion in this study is that the factors that influence anemia in pregnant women are divided into three factors, namely: External factors in the incidence of anemia in pregnant women are the use of Fe and ANC visits. Sociodemographic factors for anemia in pregnant women are living in an area of economic status and education. Of the three factors proven to be associated with the incidence of anemia in pregnant women.